A Calibration Function Built From Change Points: a Review (2017)
In this work are compared using simulation methods for estimating Breslow, Efron and exact in Cox regression, to ﬁnd the estimate of the model parameters, obtaining conﬁdence intervals by resampling the Bootstrap, Jackknife and traditional asymptotic. Are generated samples of times using the inverse of the transformation, for models of exponential regression and Weibull. It illustrates the results of the amplitudes of the conﬁdence intervals taking as a reference the regression estimate parametric. Showing the eﬃciency of these intervals.